Bayesian Bullshit - Sajan Srivastava; Tymofiy Mylovanov; Rakesh Vohra (Journal of Mechanism and Institution Design)

(untitled)
A bullshitter neither knows nor cares about the truth, and therefore, it has been asserted, is more pernicious than a liar. We examine this assertion within the standard model of cheap talk communication where a bullshitter is modeled as an uninformed Sender. We show that in some circumstances, uncertainty about whether the Sender is informed or not can increase the welfare of the Receiver.